Pengaruh Lingkungan Sosial Dan Strata Pendidikan Orang Tua Terhadap Hasil Belajar IPS Pada Siswa Kelas IV dan V MIN I Gresik - Faridatul Umah (Pedir Research Institut, 2021)
Abstract:. Student learning outcomes themselves are heavily influenced by several factors, one of which is external factors in the form of the social environment and parental education standards on social studies learning outcomes for students in grades IV and V MIN I Gresik. The research subjects involved in this study amounted to 111 students. The results of this study indicate that there is a positive correlation between the social environment and the educational strata of parents on the social studies learning outcomes of students at MIN I Gresik, the correlation is large in the social environment, the strata of parental education affects students' social studies learning outcomes by 21.9%, meaning that the social environment , the educational strata of parents in the good category.